2001
DOI: 10.1097/00000539-200106000-00049
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Perioperative Management—Combining Thoracic Epidural Analgesia, Forced Mobilization, and Oral Nutrition—Reduces Hormonal and Metabolic Stress and Improves Convalescence After Major Urologic Surgery

Abstract: We sought in this prospective study to use a multimodal approach to reduce stress and improve recovery in patients undergoing major surgery. During an initial study period, 30 patients were randomly allocated to receive general anesthesia (GA; Group 1) or a combination of GA and intraoperative thoracic epidural analgesia (TEA; Group 2) when undergoing radical cystectomy. Parenteral nutrition was provided for 5 days after surgery. During the second period, 15 patients were treated with a multimodal approach (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(88 citation statements)
references
References 12 publications
2
80
0
6
Order By: Relevance
“…Cortisol levels increased with surgery, but they determined no difference between groups. 15 Tutaş et al reported significantly high 6-h glucose values in patients undergoing laparoscopic hiatal hernia surgery and receiving EA , while there was no significant difference between the groups in terms of cortisol levels. 16 Ersoy et al reported that lumbar EA combined with GA in major abdominal surgery established hemodynamic stability and reduced stress response and sevoflurane requirements.…”
Section: Discussionmentioning
confidence: 95%
“…Cortisol levels increased with surgery, but they determined no difference between groups. 15 Tutaş et al reported significantly high 6-h glucose values in patients undergoing laparoscopic hiatal hernia surgery and receiving EA , while there was no significant difference between the groups in terms of cortisol levels. 16 Ersoy et al reported that lumbar EA combined with GA in major abdominal surgery established hemodynamic stability and reduced stress response and sevoflurane requirements.…”
Section: Discussionmentioning
confidence: 95%
“…NsNSAIDs are integral components of multimodal analgesia (Kehlet, 1997;Brodner et al, 2001;Barratt et al, 2002 ). There was no effect on pruritus, urinary retention and respiratory depression (Marret et al, 2005 Level I 5 ).…”
Section: Efficacymentioning
confidence: 99%
“…[8,9] Beyond its analgesic properties, TEA's effects on the postoperative neurohumoural stress response, cardiovascular pathophysiology, and intestinal dysfunction have been in the focus of both clinical and experimental investigations for years. [10][11][12][13][14] However, the use of TEA is related to specific complications and contraindications. Thoracic epidural allows utilization of incremental doses of local anesthetic agent which offers preservation of the respiratory function.…”
Section: Introductionmentioning
confidence: 99%